﻿Physicians' knowledge and preferences in tactics of management and rational pharmacotherapy of arterial hypertension in pregnant women (PHYGEST study) - Roman A. Bontsevich; Tatiana I. Balamutova; Natalia A. Chukhareva; Oksana V. Tsygankova; Galina A. Batisheva; Alena Paleskava; Olga G. Kompaniets; Galina G. Ketova; Valeriya O. Barysheva; Vera A. Nevzorova; Irina M. Martynenko; Sergey P. Pakhomov (Belgorod National Research University, 2022)
Introduction: The issues of rational antihypertensive therapy in pregnant women are always extremely relevant, since high blood pressure in a pregnant woman is associated with serious risks for a mother and a fetus. The aim of the study: To determine the knowledge and preferences of physicians in the management of pregnant women with arterial hypertension. Materials and methods: A multicenter study was conducted in 2018-2021 using an anonymous questionnaire among 411 doctors from 8 regions of Russia. Results and discussion: The levels of knowledge and preferences of specialists in the issues of diagnosing and formulating a diagnosis of arterial hypertension and preeclampsia in pregnant women, prescribing basic and additional drugs for the treatment and prevention of hypertension were revealed, and the degree of compliance with the current clinical guidelines was assessed. Conclusion: Due to the insufficient level of knowledge of specialists, it is required to pay increased and special attention to this problem, strengthen control over compliance with clinical guidelines, and introduce it into postgraduate recommendations and continuing education programs.